PENGGUNAAN MEDIA VISUAL MUSEUM JENDERAL SUDIRMAN DALAM PEMBELAJARAN IPS DI SMP MUHAMMADIYAH PURWOJATI KABUPATEN BANYUMAS - Priambodo, Agni; Mulyoto, M.; Djono, D. (HISTORIKA, 2015)
The Purpose of this study is to exsplore: (1) the learning plans in the use of visual media Museum Jenderal Sudirman Purwokerto, (2) the learning action in the use of visual media Museum Jenderal Sudirman Purwokerto, (3) result the learning in the use of visual media Museum Jenderal Sudirman Purwokerto, (4) the learning obstacle in the use of visual media Museum Jenderal Sudirman Purwokerto. This study is done in SMP Muhammadiyah Purwojati Kabupaten Banyumas.This study uses descriptive qualitative method. Sources of data used are informants, documents, documentations, place and event. The techniques for collecting the data are in depth interviews, observations, and document using purposive sampling technique. This study uses source triangulation, methodolical triangulation, investigator triangulation, and theory triangulation as its data validity. The data analysis technique used is interactive model include data reduction, data serving, and coclusion drawing or verification.            The result of this study are as follow: (1) in the learning plans, teacher set the SK and KD, desain the method, make RPP, prepare the media, and make questions. (2) the learning process consist of three activity steps; they are: pre activyti, main activity which consist of exsploration, elaboration, and confirmation, and post activity whisch is the last activity consist of reflection and assessment. (3) result learning in the use of visual media Museum Jenderal Sudirman Purwokerto shows succes (4) facilites and the lack of creativity of the theachers become obstacle in learning. To overcome the obstacles, the school will complete its facilities.